Mycoherbicide for water hyacinth - Beed, Fenton D. (2003)
A presentation of the theoretical approach and results of IMPECCA: International Mycoherbicide programme for Eichhornia crassipes ((Mart.) Solms) control in Africa, with particular emphasis on activities in West Africa.